The Use of RAP (Read, Ask, Put) to Improve Reading Comprehension : A Systematic Review - Novasyari, Ressy (Universitas Indo Global Mandiri, 2025)
This article aims to conduct a systematic review of using RAP (Read, Ask, Put) to improve reading comprehension. The search strategy is based on the following keywords: